Assessment of Collaboration and Feedback on Gesture Performance - Anastasiou, Dimitra; Ras, Eric; Fal, Mehmetcan (Technology Enhanced Assessment, 2019)
This paper proposes gesture performance as one main channel for assessing collaboration skills, while multiple users solve a problem collaboratively on a tangible user interface. Collaborative problem solving incorporates two dimensions, complex problem solving and collaboration. Thus, the technology-based assessment of collaborative problem solving includes assessing both problem solving and collaboration skills. Particularly, for assessing collaboration skills, we consider gesture performance as an important indicator. We differentiate between physical 3D mid-air gestures and manipulative gestures; for the latter, we developed a gesture recognition application using Kinect. The method we follow for object and gesture recognition is to merge the logging files from our tangible interface software framework (object recognition) with the Kinect log files (gesture recognition) in one file. The application can analyze the number of object manipulations with respect to timing axis, subject/participant, and handedness.